2020
DOI: 10.1016/j.neuropharm.2019.107846
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mechanisms underlying reinstatement of cigarette smoke extract- and nicotine-seeking behavior in rats

Abstract: Despite extensive research, current therapies for smoking cessation are largely ineffective at maintaining abstinence for more than a year. Whereas most preclinical studies use nicotine alone, the goal of the present study was to evaluate whether inclusion of non-nicotine tobacco constituents provides better face validity for the development of new pharmacological therapies for smoking cessation. Here, we trained adult male rats to self-administer nicotine alone or cigarette smoke extract (CSE), which contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
(93 reference statements)
1
11
0
Order By: Relevance
“…However, as compared to the addition of CSE into NS, the MAOA inhibition of non-nicotine constituents might be an important factor for the enhancement on nicotine, which would lead to stronger DA release and reinforcement properties. This is consistent with previous studies using the MAOA inhibitor (Guillem et al, 2005;Lotfipour et al, 2011;Smith et al, 2015Smith et al, , 2016 or CSE of normal nicotine content cigarettes (Costello et al, 2014;Hall et al, 2014;Gellner et al, 2016;Cross et al, 2020), but it is worth highlighting that this study complemented the effects of the mixture of non-nicotine constituents.…”
Section: Discussionsupporting
confidence: 92%
“…However, as compared to the addition of CSE into NS, the MAOA inhibition of non-nicotine constituents might be an important factor for the enhancement on nicotine, which would lead to stronger DA release and reinforcement properties. This is consistent with previous studies using the MAOA inhibitor (Guillem et al, 2005;Lotfipour et al, 2011;Smith et al, 2015Smith et al, , 2016 or CSE of normal nicotine content cigarettes (Costello et al, 2014;Hall et al, 2014;Gellner et al, 2016;Cross et al, 2020), but it is worth highlighting that this study complemented the effects of the mixture of non-nicotine constituents.…”
Section: Discussionsupporting
confidence: 92%
“…Responses on the non-reinforced (Non-Reinf) lever were recorded but had no consequences. Procedures modeled previous work ( 54 , 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nicotine-prime injections contained 0.15 mg/kg nicotine and was administered intraperitoneally immediately before the reinstatement test. The nicotine-prime dose was chosen based on previous work (26,54). Between reinstatement tests, animals were returned to extinction condition for a minimum of two days, or until extinction criteria were 10.3389/fpsyt.2022.1064211 met.…”
Section: Cue and Nicotine-induced Reinstatementmentioning
confidence: 99%
“…Indeed, some studies have shown that CSE produces a greater effect on nicotine self-administration than can be explained based solely on nicotine content, though none of these studies document in vivo MAO inhibition by CSE. Possibly the most compelling differences between self-administration of nicotine and CSE is reported by Costello et al (2014) , though this response was not replicated in subsequent studies ( Gellner et al, 2016a ; Cross et al, 2020 ; possibly because of small methodological details, Gellner et al, 2016a ). Costello et al (2014) reported that an aqueous extract of cigarette smoke increased self-administration of smaller doses of nicotine compared to nicotine alone, a shift of the nicotine dose-response curve consistent with the effects of MAO inhibition noted above; similar results were reported by Marusich et al (2019) .…”
Section: Monoamine Oxidase Inhibition By Cigarette Smoke and Nicotine...mentioning
confidence: 95%